2021
DOI: 10.3390/jtaer16040063
|View full text |Cite
|
Sign up to set email alerts
|

Peer-to-Peer Tourism: Tourists’ Profile Estimation through Artificial Neural Networks

Abstract: Peer-to-peer tourism is one of the great global trends that is transforming the tourism sector, introducing several changes in many aspects of tourism, such as the way of travelling, staying or living the experience in the destination. This research aims to determine the relationship between the sociodemographic characteristics of tourists interested in peer-to-peer accommodation and the importance they give to various motivational factors about this type of tourism in a “cultural-tourism” city. The methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…These results have followed the trends observed in other studies [7,17,44]. Thus, the positive attitudes of students can determine their intentions and behaviours towards sustainable development [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results have followed the trends observed in other studies [7,17,44]. Thus, the positive attitudes of students can determine their intentions and behaviours towards sustainable development [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 83%
“…According to Çimer and Aydin [33], the development of individuals' attitudes towards sustainability influences their intentions and sustainable behaviours. Therefore, individual sustainable attitudes affect the intention to participate in actions related to sustainable development [24][25][26][27][28][29][30][31][32][33][34]. A person with sustainable attitudes can help motivate one or more people to do so [35].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other statistical procedures that could have been applied to the dataset, such as, for example, artificial neural networks, in order to estimate a certain socio-demographic tourist profile, along the line of Moral et al [86]. However, as the aim of this work was focused on the typologies of foreign tourists based on emotional perceptions, it was considered convenient to follow the methodology explained in the previous paragraphs.…”
Section: Discussionmentioning
confidence: 99%
“…Neural network techniques are also currently used for the product-need matching process, which provide a customized solution for the customers. For example, a study revealed that neural network techniques can be applied to provide customized offers to peer-to-peer tourists on the basis of sociodemographic characteristics [42].…”
Section: Sentiment Analysis Of Ewom In Market Intelligencementioning
confidence: 99%